Silicone implant surface microtopography modulates inflammation and tissue repair in capsular fibrosis - Schoberleitner, Ines; Faserl, Klaus; Tripp, Christoph H.; Pechriggl, Elisabeth Judith; Sigl, Stephan; Brunner, Andrea; Zelger, Bettina; Hermann-Kleiter, Natascha; Baier, Leoni; Steinkellner, Theresia; Sarg, Bettina; Egle, Daniel; et al. (Frontiers in Immunology, 2024)
Excessive fibrous capsule formation around silicone mammary implants (SMI) involves immune reactions to silicone. Capsular fibrosis, a common SMI complication linked to host responses, worsens with specific implant topographies. Our study with 10 patients investigated intra-and interindividually, reduced surface roughness effects on disease progression, wound responses, chronic inflammation, and capsular composition. The results illuminate the significant impact of surface roughness on acute inflammatory responses, fibrinogen accumulation, and the subsequent fibrotic cascade. The reduction of surface roughness to an average roughness of 4 μm emerges as a promising approach for mitigating detrimental immune reactions, promoting healthy wound healing, and curbing excessive fibrosis. The identified proteins adhering to rougher surfaces shed light on potential mediators of pro-inflammatory and pro-fibrotic processes, further emphasizing the need for meticulous consideration of surface design. The composition of the implant capsule and the discovery of intracapsular HSP60 expression highlight the intricate web of stress responses and immune activation that can impact long-term tissue outcomes.